Pemikiran Mahmud Yunus dalam Pembaruan Pendidikan Islam di Indonesia - Hamzah, Syeh Hawib (IAIN Samarinda, 2014)
Mahmud Yunus is one of the pinoers of the Islamic education in Indonesia. Some of his huge important thoughts are: accommodating the Islamics lesson as an obligatory lesson in the schools, establishing the state SGHA, establishing the PGA, provoking the equality of the certificate of madrasah graduation, and pioneering the decree of Islamic Higher Education. The thoughts of Mahmud Yunus was influenced by his hometown local wisdom, his visits to middle-east nations, and the time when he was in the religious department.